MORAL VALUES FOUND IN EDUCATED BY TARA WESTOVER VIEWED FROM INDONESIA CHARACTER BASED EDUCATION - Ekky Fatma Hiastri (Language-Edu, 2021)
Recently, the lack of moral problems occurs in every single way of life. Drug abuse, violence, bullying, pornography and prostitution are the general examples of moral degradation issues. Therefore, education called as the factors that humans really need to prevent ourselves from harmless or negative influence. This study conducted to find types moral values found in “Educated” a novel by Tara Westover and the implementation of moral values in character based education by using the theory of Universal Moral Values by Kinnier et. al and Research and Development Agency for the Curriculum Centre states that there are 18 National Character and Cultural Education Values that standardize the values of Indonesia’s Education. The primary data is taken from “Educated” novel in the form of narrations and the secondary data is from previous studies in the form statements, ideas or background setting which comes from analysis and the findings. This research was conducted using descriptive qualitative method, it focuses on describing and interpreting the moral values in descriptive. The result of this study showed that there 13 moral values found in the novel and these finding can be implemented in the character based education in Indonesia.